Leishmania (Viannia) braziliensis Inositol Phosphorylceramide: Distinctive Sphingoid Base Composition - De Castro Levatti, Erica V.; Toledo, Marcos S.; Watanabe Costa, Renata; Bahia, Diana; Mortara, Renato A.; Takahashi, Helio K.; Straus, Anita H. (Frontiers in Microbiology, 2017)
Inositol phosphorylceramide (IPC), the major sphingolipid expressed in the genus Leishmania but not expressed in mammals, is considered a potentially useful target for chemotherapy against leishmaniasis. Leishmania (Viannia) braziliensis is endemic in Latin America and causes American tegumentary leishmaniasis. We demonstrated that IPCs are localized internally in parasites, using a specific monoclonal antibody. Treatment with 5 µM myriocin (a serine palmitoyltransferase inhibitor) rendered promastigotes 8-fold less infective than controls in experimental hamster infection, as determined by number of parasites per inguinal lymph node after 8 weeks infection, suggesting the importance of parasite IPC or sphingolipid derivatives in parasite infectivity or survival in the host. IPC was isolated from promastigotes of three L. (V.) braziliensis strains and analyzed by positive- and negative-ion ESI-MS. The major IPC ions were characterized as eicosasphinganine and eicosasphingosine. Negative-ion ESI-MS revealed IPC ion species at m/z 778.6 (d20:1/14:0), 780.6 (d20:0/14:0), 796.6 (t20:0/14:0), 806.6 (d20:1/16:0), and 808.6 (d20:0/16:0). IPCs isolated from L. (V.) braziliensis and L. (L.) major showed significant differences in IPC ceramide composition. The major IPC ion from L. (L.) major, detected in negative-ion ESI-MS at m/z 780.6, was composed of ceramide d16:1/18:0. Our results suggest that sphingosine synthase (also known as serine palmitoyltransferase; SPT) in L. (V.) braziliensis is responsible for synthesis of a long-chain base of 20 carbons (d20), whereas SPT in L. (L.) major synthesizes a 16-carbon long-chain base (d16). A phylogenetic tree based on SPT proteins was constructed by analysis of sequence homologies in species of the Leishmania and Viannia subgenera. Results indicate that SPT gene position in L. (V.) braziliensis is completely separated from that of members of subgenus Leishmania, including L. (L.) major, L. (L.) infantum, and L. (L.) mexicana. Our findings clearly demonstrate sphingoid base differences between L. (V.) braziliensis and members of subgenus Leishmania, and are relevant to future development of more effective targeted anti-leishmaniasis drugs.